2013
DOI: 10.1007/s00253-013-5066-8
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome analysis of Escherichia coli exposed to immobilized anthraquinone-2-sulfonate and azo dye under anaerobic conditions

Abstract: The immobilization of quinone compounds is regarded as a promising strategy to accelerate anaerobic decolorization of xenobiotic compounds azo dyes in the presence of quinone-reducing microorganisms. However, little is known about the basic response of these microorganisms to immobilized quinones in the presence of azo dyes. In the present study, whole-genome DNA microarrays were used to investigate a quinone-reducing bacterium Escherichia coli K-12 transcription response to immobilized anthraquinone-2-sulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…However, our GTA showed that in the SA-producing strain PB12.SA22, the galP gene was not significantly upregulated during EXP growth and the STA phase. This result was also observed in GTA for the parental strain PB12 in the same culture conditions (data not shown), suggesting that in both strains grown in complex fermentation broth for SA production, the OMP OmpC, LamB, and the maltose ABC transporter, have an important role in the transport of glucose because previous works reported the participation of these proteins in the uptake of glucose in E. coli [20-23]. All these genes were found to be upregulated in the EXP and STA1 phases, associated with the consumption of >30% of the initially added glucose to the fermentation broth; however, only in the STA1/STA2 comparison was detected the upregulation of ompC .…”
Section: Discussionsupporting
confidence: 66%
“…However, our GTA showed that in the SA-producing strain PB12.SA22, the galP gene was not significantly upregulated during EXP growth and the STA phase. This result was also observed in GTA for the parental strain PB12 in the same culture conditions (data not shown), suggesting that in both strains grown in complex fermentation broth for SA production, the OMP OmpC, LamB, and the maltose ABC transporter, have an important role in the transport of glucose because previous works reported the participation of these proteins in the uptake of glucose in E. coli [20-23]. All these genes were found to be upregulated in the EXP and STA1 phases, associated with the consumption of >30% of the initially added glucose to the fermentation broth; however, only in the STA1/STA2 comparison was detected the upregulation of ompC .…”
Section: Discussionsupporting
confidence: 66%
“…This was because many genes with iron and copper acquisition were up-regulated, which might have increased the concentration of copper in the E. coli 381 cytoplasm 47 , 87 . The repression of some genes encoding phage shock proteins may be due to different environmental stress conditions in E. coli , which fortified the resistant character of strain 88 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the data from Regprecise (http://regprecise.lbl.gov/), transcriptional factor NarP, regulated by RpoS, potentially regulated MtrCBA, MtrFED, OcmA, and OmpW, as well as a global regulator CRP (cyclic AMP receptor protein) in Shewanella spp., since the DNA binding sites where NarP activates their expressions were localized upstream of the coding regions. In addition, although azo dyes are toxic to S12, we did not find significant effects of the genes encoding transcriptional regulators of the MarR family, which determine the tolerance of E. coli to antibiotics, organic solvents, and oxidative stress, as well as azo dyes (62,73). It seems therefore that different regulative systems existed in S. decolorationis S12 and E. coli.…”
Section: Transcriptional Modulations Concerning Amaranth Degradation mentioning
confidence: 56%